Legal and regulatory challenges in controlling heavy metal and chemical pollutants in geochemical cycles - Rami Salih; Sundus Serhan Ahmed; Sarah Aamer Riyadh Abdulrahman; Noor Sabah Abd-Al Latif Jasim; Baker Mohammed Khalil (Environment and Social Psychology, 2025)
Huge number of heavy metals and chemical contaminants are scattered all over geochemical systems and tested in the face of constant hazard of environmental quality, human health, and governmental control. The influence of the environmental matrices on the spatial distribution, mobility and retention of lead (Pb), cadmium (Cd) and arsenic (As) was studied in five sites with varying environmental peculiarities in terms of industrial, agricultural, mining and waste related activities. In this study, different conventional methods have been used to explore the contamination of heavy metals in an untreated industrial wastewater (field sampling) and after treatments with atomic absorption spectrometry technique performed in a laboratory using a batch of adsorption tests and multivariate statistical analysis. Results suggest there may be a high spatial variability in the concentration levels of metal with land use derived patterns and geochemical properties as likely principal contributors to site-specific variation. Correlation and regression analyses showed that pH and electrical conductivity influenced the mobility of metals, especially arsenic, to a greater extent. The metals retention by adsorption as well presented non-uniform other retention behavior able to be reflected in their environmental persistence and potentially different mobility. To identify the hotspots of remediation, spatialization was performed. Combining this and the results would show how a localized geochemical profiling is important toward improving of understanding about pollutants dynamic patterns, localities in environmental management. These findings are also favorable to the idea of injecting science into the law system; that legal interests would be able to protect both environment and regulatory. This may be suggested for the future study to scaling up the spatial and temporal investigation, inclusion of chemical speciation examination of metals analysis and application of advanced predictive model in assessment. It is also suggested in the analysis that data should be harmonized to meet geochemical interpretation in accordance with the international environmental law as in Basel and Minamata conventions in order to meet the standards of the management of pollutions. It raises the level of application of the environmental geochemistry considerations in policy options and transboundary governance frameworks, by emphasizing the legal factuality of scientific facts.